Spectral Absorbance of Dye Indicator in Relation to Liquid-Liquid Interactions: Aryl Amines, Acetone and Hexane - N. Modi, Ashvin; Patel, Dinesh; Desai, C.M. (Asian Journal of Chemistry, 2010)
Molecular interactions of binary organic liquids have beenstudied by several authors. In the present work the molecular interactionsof binary mixtures of aniline, p-toluidine, 2,6-diethyl anilinewith acetone or n-hexane in polar solvent methanolspectrophotometrically by mono-variation method using dye indicator have been studied.